2012
DOI: 10.1371/journal.pone.0031571
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soybean Global Gene Expression after Application of Lipo-Chitooligosaccharide from Bradyrhizobium japonicum under Sub-Optimal Temperature

Abstract: Lipo-chitooligosaccharides (LCOs), signal compounds produced by N2-fixing rhizobacteria after isoflavone induction, initiate nodule formation in host legumes. Given LCOs' structural similarity to pathogen-response-eliciting chitin oligomers, foliar application of LCOs was tested for ability to induce stress-related genes under optimal growth conditions. In order to study the effects of LCO foliar spray under stressed conditions, soybean (Glycine max) seedlings grown at optimal temperature were transferred to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 91 publications
(102 reference statements)
1
16
0
Order By: Relevance
“…Previously, we showed that treatment with a chitin 8mer elicited a host defense-related cellular response in Arabidopsis similar to that induced by CHH in Arabidopsis [18,26]. The induction of specific defense-related genes after treating Arabidopsis with CHH, has also been documented by other groups experimenting with Arabidopsis [21,50,51], rice and soybean [19,52,53,54]. Our results showed that chitin 4mer treatment induced an expression pattern that was distinct from the pattern observed after 8mer or CHH treatments.…”
Section: Discussionmentioning
confidence: 61%
“…Previously, we showed that treatment with a chitin 8mer elicited a host defense-related cellular response in Arabidopsis similar to that induced by CHH in Arabidopsis [18,26]. The induction of specific defense-related genes after treating Arabidopsis with CHH, has also been documented by other groups experimenting with Arabidopsis [21,50,51], rice and soybean [19,52,53,54]. Our results showed that chitin 4mer treatment induced an expression pattern that was distinct from the pattern observed after 8mer or CHH treatments.…”
Section: Discussionmentioning
confidence: 61%
“…An increase in mycorrhizal colonization (Gigaspora margarita) was observed in Pinus abies treated with LCO [50,58]. Recent research in our laboratory, on soybean leaves treated with LCOs under sub-optimal growth conditions, revealed the up-regulation of over 600 genes, many of which are defense and stress response related, or transcription factors; microarray results show that the transcriptome of the leaves is highly responsive to LCO treatment at 48 h post treatment [59]. These results suggest the need to investigate more carefully the mechanisms by which microbe-to-plant signals help plants accommodate abiotic and biotic stress conditions.…”
Section: Lipo-chitooligosaccharide (Lco) From Bradyrhizobium Japonicummentioning
confidence: 93%
“…These include bacteria in the soil near plant roots, on the surface of plant root systems, in spaces between root cells or inside specialized cells of root nodules; they stimulate plant growth through a wide range of mechanisms ( Gray and Smith, 2005 ; Mabood et al, 2014 ), such as: (1) nutrient solubilization (particularly phosphorus – Boddey et al, 2003 ; Kennedy et al, 2004 ; Trabelsi and Mhamdi, 2013 ), (2) production of metal chelating siderophores, (3) nitrogen fixation ( Vessey, 2003 ; Bhattacharyya and Jha, 2012 ; Drogue et al, 2012 ), (4) production of phytohormones, (5) production of 1-aminocyclopropane-1-carboxylate deaminase, (6) production of volatile organic compounds, (7) induction of systemic resistance [induced systemic resistance (ISR) and systemic required resistance (SAR) – Jung et al, 2008b , 2011 ], and (8) suppression of disease through antibiosis ( Bhattacharyya and Jha, 2012 ; Spence et al, 2014 ). It has also been shown that “signal” compounds produced by bacteria in the phytomicrobiome stimulate plant growth ( Prithiviraj et al, 2003 ; Mabood et al, 2006a ; Lee et al, 2009 ), particularly in the presence of abiotic stress ( Wang et al, 2012 ; Subramanian, 2014 ; Prudent et al, 2015 ). In the broadest sense PGPR include legume-nodulating rhizobia.…”
Section: The Phytomicrobiome and Plant Growthmentioning
confidence: 99%